Prognostic impact of beta-blocker compared to combined amiodarone therapy secondary to ventricular tachyarrhythmias - Schupp, Tobias; Behnes, Michael; Reiser, Linda; Kern-Bollow, Armin; Taton, Gabriel; Reichelt, Thomas; Ellguth, Dominik; Engelke, Niko; Ansari, Uzair; El-Battrawy, Ibrahim; Weiß, Christel; Lang, Siegfried; et al. (International journal of cardiology, 2019)
Objective The study sought to assess the prognostic impact of treatment with beta-blocker (BB) compared to combined BB plus amiodarone (BB-AMIO) on long-term survival in patients surviving ventricular tachyarrhythmias on admission. Background Data regarding the prognostic outcome of patients presenting with ventricular tachyarrhythmias treated with BB and BB-AMIO is limited. Methods A large retrospective registry was used including consecutive patients surviving index episodes of ventricular tachyarrhythmias from 2002 to 2016. Patients treated with BB were compared to patients with BB-AMIO. The primary prognostic endpoint was long-term all-cause death at 3years. Kaplan-Meier, multivariable Cox regression and propensity score matching analyses were applied. Results A total of 1354 patients was included, 85% treated with BB, 15% with BB-AMIO. Within the unmatched real-life cohort, uni- and multivariable Cox regression models revealed BB associated with improved long-term survival compared to BB-AMIO (univariable: HR=0.550; p=0.001, multivariable: HR=0.712; statistical trend, p=0.052). After propensity-score matching (n=186 matched pairs), BB therapy was still associated with improved survival compared to BB-AMIO (mortality rate 18% versus 26%; log rank p=0.042; HR=0.634; 95% CI=0.407-0.988; p=0.044). Prognostic superiority of BB was mainly observed in patients with LVEF≥35% (HR=0.463; 95% CI=0.215-0.997; p=0.049) and in those without atrial fibrillation (non-AF) (HR=0.415; 95% CI=0.202-0.852; p=0.017). Conclusion BB therapy is associated with improved secondary long-term prognosis compared to BB-AMIO in patients surviving index episodes of ventricular tachyarrhythmias.
Available online 15 November 2018
Gesehen am 18.02.2019